Konsep Autism Design Index ASPECTSS dalam Perancangan Interior Ruang Kelas Anak Penyandang Autisme di Sekolah Dasar Luar Biasa - Ardian Ariatsyah; Zulfikar Taqiuddin; Finkanaia Wahab; Siti Zulfa Yuzni (Jurnal Serambi Engineering, 2024)
Traditional classroom settings often present significant challenges for children with autism spectrum disorder (ASD) in terms of communication. Specialized classrooms designed for children with ASD, such as those based on the Autism Design Index (ASPECTSS), incorporate specific principles and approaches including navigation patterns, lighting, and color. This study aimed to evaluate the effectiveness of classroom designs based on the ASPECTSS in improving communication skills and academic achievement of students with ASD. Employing a mixed-methods approach, this study compared the responses of students with ASD in two different classroom conditions. The results indicated that students with ASD responded more positively to classrooms designed based on the Autism Design Index ASPECTSS, as evidenced by increased verbal communication frequency, attention span, and academic performance. These findings suggest that physical classroom design tailored to the sensory and cognitive needs of students with ASD can serve as an effective intervention to support their learning. This study recommends that schools adopt ASPECTSS principles when designing inclusive classrooms to create optimal learning environments for all students.